Exploring willingness to pay for health insurance and preferences for a benefits package from the perspective of women from low-income households of Karachi, Pakistan - Shifa Salman Habib; Shehla Zaidi (BMC, 2021)
Abstract Background Achieving universal health coverage (UHC) and reduction in out of pocket (OOP) expenditures on health, is a critical target of the Sustainable Development Goals (SDG). In low-middle income countries, micro-health insurance (MHI) schemes have emerged as a useful financing tool for laying grounds for Universal Health Coverage. The aim of this study was to provide evidence for designing a feasible health insurance scheme targeted at urban poor, by exploring preferences for an insurance benefits package and co-payments among women from low-income households in Karachi, Pakistan. Methods This was a descriptive cross-sectional study, conducted using household surveys between July-August 2015. A total of 167 female beneficiaries of Benazir Income Support Programme (BISP), a large-scale cash transfer scheme targeted at low-income households, were recruited in Karachi through a mix of convenience and snowball sampling. Hypothetical insurance benefits packages for a prospective health insurance scheme were formulated to capture respondents' preferences for health insurance benefits package and co-payments. All data was analyzed using Stata (version 13). Results Respondents reporting expenditure on OPD and hospitalization in the last 2 weeks were 93.4 and 11.9% respectively. The highest median expenditure was incurred on medicines. Out of the proposed benefits package, a majority (53%) of the study participants opted for the comprehensive benefits package that provided coverage for emergency care, hospitalization, OPD consultation, diagnostic tests and transportation. For the co-payment plan, 38.9% participants preferred no co-payments that is 100% insurance coverage of medicines followed by hospitalization (25.9%). Nearly half of the respondents (49.4%) chose outpatient consultation for 50% co-payment. A majority of the participants (65.3%) agreed to 100% co-payment for the transportation cost. Conclusion Health insurance schemes can be introduced in urban areas, against collection of micro-payments, to prevent low-income households from facing financial catastrophe. A comprehensive benefits package covering emergency care, hospitalization, OPD consultation, diagnostic tests and transportation, is the most preferred among low-income beneficiaries.